How European is European Identification? Comparing Continental Identification in Europe and Beyond. (13th December 2012) - Roose, Jochen
Abstract European identification has previously been explained by the selective gains brought by the European integration process, by personal transnational experiences and by the influence of political programmes aiming at increasing levels of identification. All these explanations imply that identification with one's continent would be specific in extent and distribution across the social structure in Europe compared to other continents. These assumptions are tested using International Social Survey Programme (ISSP) and a longitudinal analysis using Eurobarometer. Results show that, first, the extent of continental identification in Europe is not higher than in other continents. Second, they reveal that there has been no increase in European identification in recent decades. And third, the socio‐structural distribution of continental identification is similar on all continents. Accordingly, explaining European identification with respect to policy output of the European Union is questioned by the findings. The results rather hint at the possibility that European identification is independent of political integration.